Job satisfaction factors among bank employees in Cyberjaya - Kaaminiy, Sidharthan (2018)
Job satisfaction is defined how contented an employee is in his workplace. The way people feel about their job and factors that influences it. It represents both positive and negative feeling that an employee has towards their job at their workplace. The aim of this study is to identify the factor that influence job satisfaction among employees in several banks in Cyberjaya area. Besides that, the researcher would like to determine the factors that impact job satisfaction at workplace such as work environment, salary, supervisor relationship, co-worker relationship and training. The objectives of this study is to determine the level of job satisfaction among bank employees in several banks and factors affecting it such as relationship between work environment, salary, supervisor, training and coworker and their significant impact towards job satisfaction. This research is done to help the business and higher management keep employees satisfied and reduce turnover in the long run and yield profit for the organization. The targeted for the test were selected randomly and contacted for their willingness to participate in the research. Questionnaires were then distributed to the employees after their working hours. About 200 of bank employees are involved in this research. Upon completing the survey and analyzing in SPSS software, salary and training are the highest factor that influences job satisfaction among bank employees. Supervisor relationship has a moderate effect towards job satisfaction. However co-worker relationship and work environment has a low effect on job satisfaction. In conclusion, it is imperative for the Human Resource Management to boost high job satisfaction among staff in the banking industry. It is also important to stress that good remuneration and scheduled trainings escalate staff performances and in turn improve the quality of the banking industry.